Digital light processing 3D printing with thiol–acrylate vitrimers. Issue 5 (14th December 2020) - Rossegger, Elisabeth; Höller, Rita; Reisinger, David; Strasser, Jakob; Fleisch, Mathias; Griesser, Thomas; Schlögl, Sandra
Abstract : The customized fabrication of soft active devices with self-healing function is demonstrated by 3D printing with vitrimeric thiol–acrylate photopolymers. Abstract : Dynamic covalent bonds endow polymer networks with advanced functions such as self-healability, recyclability, malleability and shape memory. Currently, the most attractive dynamic networks are vitrimers, which rely on thermo-activated exchange reactions such as the catalyzed transesterification of hydroxyl ester moieties. However, the introduction of dynamic covalent bonds into 3D printable photopolymers is challenging, as commonly used transesterification catalysts are poorly soluble and compromise on cure rate and pot life of photocurable resins. Herein, a mono-functional methacrylate phosphate is presented as new transesterification catalyst, which overcomes these limitations and unlocks a new toolbox of photocurable vitrimers. Applied in thiol–acrylate vitrimer systems, the fast photopolymerization together with a high storage stability enables the successful additive manufacturing of precise 3D objects with features of 500 μm using bottom-up digital light processing (DLP). Once photo-cured, the dynamic thiol-click networks are able to rapidly undergo thermo-activated rearrangements of their network topology as shown by stress relaxation experiments. The DLP printing of soft active structures with triple-shape memory and thermal mendability is demonstrated. Its versatility makes this unique class of material an ideal candidate for 3D printing of structural and fast acting functional devices in soft robotics, biomedicine and electronics.